Formation of Nouns and Adjectives from Roots with Unādi Rules - Maya, Yanthawat (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Uṇadi is a group's name of suffixes which placed at the end of Dhātus (verbal roots) to make nouns and adjectives. It's already been fixed by the first suffix's name Uṇ which was defined to be represent whole suffixes. In consequence Uṇādi is a meaning of the suffix group to begin with Uṇ suffix in the first instance accordingly, due to the fact that there are many suffixes in this group. The formation of nouns with approach of Uṇādi suffixes is similar to Kṛdanta suffixes except, when the formation approach of Kṛdanta suffixes have accomplished form they can be usable to verb or noun term, but the formation approach of Uṇādi suffixes have accomplished form they can be usable to noun and adjective term only. The study of noun and adjective formation approach from Dhātus (verbal roots) with Uṇādi sūtras (Uṇādi rules.) through this formation approach of Uṇādi suffixes could be helpful to understand about etymology each word in Sanskrit excellently. Nevertheless the formation of nouns in sanskrit have many approach, but the formation approach of Uṇādi sūtras (Uṇādi rules.) is the most well known. The multiplicity form of Uṇādi sūtras (Uṇādi rules.) was exhibited by own obviously by the rule "Uṇādayo bahulam. (pā.sū. 3.3.1)" (The suffixes Uṇ and the rest with the force of the present and with a sense simply appellative are attached diversely.)